1990
DOI: 10.1038/eye.1990.53
|View full text |Cite
|
Sign up to set email alerts
|

The corneal endothelium

Abstract: The endothelium is a monolayer of cells on the posterior corneal surface that transports water from the stroma into the anterior chamber. This movement of water counters a natural tendency for the stroma to swell and is necessary to maintain a transparent cornea. Embryologic studies, in particular the demonstration of the derivation of the endothelium from the neural crest, have provided insight into the factors that govern the response of this tissue to disease. In some species the endothelium can regenerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
183
2
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(207 citation statements)
references
References 323 publications
9
183
2
13
Order By: Relevance
“…However, AMANN et al (2003) concluded using specular microscopy and histological methods that human corneal endothelium has a higher density in peripheral regions compared with the central region. Normally, corneal endothelium is a monolayer consisting mostly of hexagonal cells, but may have four, five, seven, or even eight sides (TUFT & COSTER, 1990;DOUGHTY, 1998). Results of previous studies reported no significant difference in polymorphism according to age (SPERLING 1977;GWIN et al, 1982) and the lack of differences in relation to endothelial parameters obtained from the bulbs of the right and left eyes in dogs, pigs, horses, and cats (GWIN et al, 1982;ANDREW et al, 2001;AMANN et al, 2003;TAMAYO-ARANGO et al, 2009;FRANZEN et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, AMANN et al (2003) concluded using specular microscopy and histological methods that human corneal endothelium has a higher density in peripheral regions compared with the central region. Normally, corneal endothelium is a monolayer consisting mostly of hexagonal cells, but may have four, five, seven, or even eight sides (TUFT & COSTER, 1990;DOUGHTY, 1998). Results of previous studies reported no significant difference in polymorphism according to age (SPERLING 1977;GWIN et al, 1982) and the lack of differences in relation to endothelial parameters obtained from the bulbs of the right and left eyes in dogs, pigs, horses, and cats (GWIN et al, 1982;ANDREW et al, 2001;AMANN et al, 2003;TAMAYO-ARANGO et al, 2009;FRANZEN et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial alterations are considered important parameters of surgical trauma and are essential in estimating the safety of surgical techniques (Tuft & Coster 1990). Currently, scanning electron microscopy and specular microscopy are used and accepted methods to evaluate the corneal endothelium (Yee et al 1987, Abib & Barreto, 2001, Andrew et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Ageing results in a gradual reduction in endothelial cell density and an increase in cell area variability in those species that exhibit minimal mitotic potential (Jackson et al 1995). Furthermore, morphological changes of endothelium associated with cell loss occur in many conditions including corneal dystrophies, keratoconus, glaucoma, uveitis, blunt ocular trauma, cataract ex-traction, and penetrating keratoplasty (Olsen 1980, Tuft & Coster 1990.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies conducted using SEM demonstrated that the corneal endothelial cells have cilia and microvillus (Tuft & Coster 1990, Pigatto et al 2005, Pigatto et al 2008. Humans and rabbits have twenty to thirty microvilli in the cell superficies, and these structures react to tox- ic substances changing their sizes (Collin & Collin 1998).…”
Section: Discussionmentioning
confidence: 99%